Expanding the diversity of DNA base modifications with N6-methyldeoxyadenosine. Issue 1 (December 2016) - Meyer, Kate; Jaffrey, Samie
Abstract Vertebrate DNA is subjected to epigenetic base modifications that have been thought to be limited to methylated and other modified forms of cytidine. A recent study shows that methylation of adenine to formN 6 -methyladenine is a rare but readily detectable modification that can be mapped to distinct genomic sites in vertebrates.